NON-DISCLOSURE OF FINANCIAL STATEMENTS OF PUBLIC COMPANIES AS AN ECONOMIC OFFENSE IN THE REPUBLIC OF SERBIA - Kostic, Marija; Mizdraković, Vule M.; Mitic, Vladimir (NBP. Nauka, bezbednosti, policija, 2021)
The successful functioning and development of the capital market, along with the possibility of attracting new investments is largely contingent on the quality of financial reporting and the availability of the statements themselves. In view of the fact that the new Law on Accounting of the Republic of Serbia came into force, the question arises to what extent public companies respect legally prescribed deadlines for submitting their statements and by doing so do not commit an economic offense. The primary goal of this paper is to draw attention to the importance of a standardized and efficient legal framework that obliges public companies to publish financial statements in a timely manner. A survey was conducted that encompassed 416 public companies listed on the Belgrade Stock Exchange and their corresponding financialstatements for 2018, as the reporting period. We tried to establish whether the sampled companies disclosed their statements within the deadline prescribed by the Law on Accounting (Law on Accounting, Official Gazette of RS, 62/2013, 30/2018). The results show that most companies disclosed financial statements during the period when they are still considered useful to potential and existing investors. Nevertheless, practice showed that there was room for improvement, and this was achieved with the adoption of the new Law on Accounting, which took effect on January 1, 2020. It integrates the deadline for compiling and disclosing statements, which in fact shortens the time period during which information on the companies’ operations should be made available to the general public and potential investors.
Keywords: Law on Accounting, financial reporting, investments, commercial offence, Republic of Serbia.